IMPLEMENTATION OF THE SYMMETRIC CRYPTOGRAPHIC ALGORITHMS RC2 AND TRIPLE DES IN ECB MODE USING CRYPTOGRAPHIC SOFTWARE PROGRAM CRYPTOOL: IMPLEMENTATION OF THE SYMMETRIC CRYPTOGRAPHIC ALGORITHMS RC2 AND TRIPLE DES IN ECB MODE USING CRYPTOGRAPHIC SOFTWARE PROGRAM CRYPTOOL - Boyanov, Petar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2024)
This paper presents an in-depth analysis of symmetric key cryptographic algorithms, focusing on RC2 and Triple DES (ECB) as implemented in CrypTool. It is widely used educational software that demonstrates various cryptographic algorithms and methods. This paper aims to provide a foundational understanding of CrypTool, explain the functionalities of RC2 and Triple DES in Electronic Codebook (ECB) mode and evaluate their performance and security.